105k views
2 votes
Zacharias is using the quadratic formula to solve the equation 0 = –2x2 + 5x – 3. He begins by substituting as shown.

Quadratic formula: x = StartFraction negative b plus or minus StartRoot b squared minus 4 a c EndRoot Over 2 a EndFraction
Substitution: x = StartFraction negative 5 plus or minus StartRoot 5 squared minus 4(2)(negative 3) EndRoot Over 2(negative 2) EndFraction
What error did Zacharias make?

The –5 should be 5.
The 52 should be –52.
The 2 in the numerator should be –2.
The 2 in the denominator should be –2.

User Yoojung
by
4.7k points

2 Answers

4 votes

Answer:the third option

Step-by-step explanation:

2,-2

User Peeter Joot
by
5.5k points
1 vote

Answer:

  • Third option: The 2 in the numerator should be –2.

Step-by-step explanation:

These are the steps made by Zacharias:

  • Quadratic formula:


  • x=(-b+/-√(b^2-4(a)(c)) )/(2a)


  • x=(-5+/-√(5^2-4(2)(-3)) )/(2(-2))

The equation to be solved using the quadratic formula is:


  • 0=-2x^2+5x-3

The parameters a, b, and c used in the quadratic formula correspond to the parameters in the general form:


  • ax^2+bx+c=0

Thus, you have:


  • a=-2,b=5,c=-3

And when you substitute you get:


  • x=(-5+/-√((-5)^2-4(-2)(-3)) )/(2(-2))


  • x=(-5+/-√((5)^2-4(-2)(-3)) )/(2(-2))

(since the -5 in the radicand is raised to an even power, you can omit the negative sign).

Now you can see that the error that Zacharias made was that the 2 in the numerator (in the radicand) should be - 2.

User Luisgabriel
by
5.0k points